Local open government issues: Experiences from Jalisco, Mexico - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim; Lestari, Reski (Journal of Law, Administration, and Social Science, 2025)
This study aims to analyze the main issues of open government in Jalisco, Mexico. Jalisco plays a leading role as the only pilot local government program of Open Government Partnership in the country. A qualitative approach and bibliometric analysis method were used in this study. The research data were obtained from the official website of the Government of Jalisco and sourced from the Google Scholar database. The findings of this study indicate that the study of open government in Jalisco is not popular. The topics that dominate the study of open government in Jalisco include transparency, corruption, citizen participation, accountability, and youth. While the latest and potential topics include transparency portal, health system, regulatory oversight, electoral participation, security, tax collection, and digital party. Jalisco is currently focusing on three main commitments of their open government, which include harmonization, unification, transparency, and corruption control in the Rules of Operation (ROP) of social programs aimed at Civil Society Organizations (CSOs); strengthening and incorporation of new elements in the digital platform for citizen participation in the creation and modification of laws; and preparation of an annex of sentences, with a clear and understandable wording, oriented to priority groups. These commitments have the potential to create a more open Jalisco government.